LABEL ANALYSIS WITH PRODUCTS OF PLANT ORIGIN - Corrêa da Silva, Jéssica; Salete Monteiro Vieira e Silva, Maria; Pereira Nóbrega, Mariana; Peixoto Vianna, Marina; Cristina Paiva, Kelli (Health and Society, 2023)
The objective of the research work was to analyze labels of industrialized vegetable cheeses, from different brands, to verify if they are within the norms of the current legislation and if they are sources of protein and calcium like traditional cheeses of animal origin. The field research took place in the city of Ribeirão Preto with a quantitative method for information analysis, the brands’ own websites and the “Desrotulando” application. The collected data were analyzed using a simple Excel spreadsheet, using a checklist as a basis for evaluation, created by the requirements of current legislation. The laws used for consultation were: Ministry of Health/National Health Surveillance Agency: RDC 429, of October 8, 2020; RDC 259 of September 20, 2002; Normative Instruction IN 75 of October 8, 2020. Ministry of Agriculture, Livestock and Supply: Normative Instruction IN 22 of November 24, 2005. Most of the information described in the labels studied is in accordance with the requirements prescribed in the legislation used as a parameter study, but none of the cheeses are sources of protein and calcium, since most are based on some oilseeds such as cashew nuts, mixed with some carbohydrate source such as starch to give cheese consistency, together with flavorings, suggestion is that companies change the nomenclature format for this type of product, together with the insertion of specific legislation for vegetable cheeses, both for production and for labeling.